توصيف عزلات Bacillus thuringiensis المعزولة من التربة السورية واختبار فاعليتها ضد يرقات فراشة طحين البحر الأبيض المتوسط Ephestia kuehniella (Lepidoptera: Pyralidae) - أحمد, محمد; كبيبو, عيسى; مهيار, مايسة (Latakia University Journal -Biological Sciences Series, 2019)
جرى البحث على ترب بعض النظم الطبيعية والزراعية في سوريا للبكتريا الممرضة للحشرات Bacillus thuringiensis. تبين من خلال فحص المستعمرات البكتيرية بالإعتماد على الشكل المورفولوجي للبلورات والاختبارات الكيميائية الحيوية أن %97 من العزلات تابعة لبكتيريا B. thuringiensis، مما يشير إلى أن بكتيريا B. thuringiensis متوافرة بغزارة في الترب السورية المدروسة. صنفت 219 عزلة من بكتيريا B. thuringiensis الى 8 تحت أنواع بمساعدة الاختبارات البيوكيميائية وهي: تحت نوع kurstaki B. thuringiensis subsp. وكان الأكثر شيوعا". وتحت الأنواع: biotype 9، thuringiensis، kenyae، sotto، dendrolimus،finitimus like- و.pakistani وجد أن 192عزلة (88%) من أصل 219 عزلة سامة للعمر اليرقي الثالث لفراشة طحين البحر الأبيض المتوسط Ephestia kuehniella، أعطت 50 عزلة منها نسبة قتل أعلى من 50 %. كما أظهرت النتائج أن فاعلية العزلات التي تحتوي على بلورات ذات شكل معين bipyramidal أعلى من فاعلية العزلات المحتوية على بلورات كروية الشكل. The occurrence of entomopathogenic bacterium Bacillus thuringiensis was investigated for some natural ecosystems in Syrian coastal plain soils. In the present study, B. thuringiensis was found in all tested ecosystems in Syria. Among the examined colonies based on crystal protein formation and biochemical tests, the proportion identified as B. thuringiensis was 97%, that indicate that B. thuringiensis was highly abundant in Syrian soils. Tow hundred and nineteen strains were found belonging to eight biochemical types with B. thuringiensis subsp. kurstaki being the most common. The other biochemical types were referable to biotype 9, thuringiensis, kenyae, sotto, dendrolimus, like- finitimus and pakistani. Of the 219 strains 192 (88%) were toxic to the third instar larvae of Ephestia kuehniella, where 50 isolates caused more than 50% mortality. The frequency of toxicity was greater in strains that produced bipyramidal parasporal crystals rather than strains produced spherical crystals.